Stepping through heritage: symbolism and meaning of Baba Nyonya beaded shoes - Nur Emylia Natasha Muchamad Imron,; Liza Marziana Mohammad Noh, (Penerbit Universiti Kebangsaan Malaysia, 2025)
The Baba Nyonya beaded shoes, or kasut manek, are more than decorative items; they are cultural symbols of the Peranakan Chinese community. Hand-sewn with colorful glass beads, these shoes reflect the fusion of Chinese, Malay, and European influences, showcasing the unique multicultural heritage of the Baba Nyonya. The intricate motifs, often featuring flowers, birds, or butterflies, carry deep meanings linked to femininity, prosperity, and tradition. Historically, kasut manek were worn during weddings and festivals, symbolizing elegance and social status. Their creation also served as a form of domestic education for Peranakan women, teaching them patience, artistry, and cultural values. This article examines the cultural significance of kasut manek through its historical context, artistic design, and its role in preserving identity. By examining visual elements, artisan interviews, and relevant literature, the study reveals how these shoes serve as vessels of cultural memory, transmitting Peranakan values across generations. Despite modern changes, the craft remains a living tradition, highlighting the enduring role of kasut manek as both an art form and a symbol of identity. Through this lens, the beaded shoes are celebrated not only for their beauty but also for their role in maintaining the legacy of the Baba Nyonya community